2020
DOI: 10.1111/liv.14548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MAFLD and NAFLD diagnostic criteria in real world

Abstract: Background and aims Metabolic associated fatty liver disease (MAFLD) is a novel concept proposed in 2020, the utility of which has not been tested and validated in real world. We aimed to compare the characteristics of MAFLD and non‐alcoholic fatty liver disease (NAFLD). Methods The data was retrieved from the third National Health and Nutrition Examination Surveys of the United States, which is an unbiased survey dataset and frequently used for the study of fatty liver disease. Results A total of 13 083 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
404
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 434 publications
(478 citation statements)
references
References 20 publications
20
404
4
7
Order By: Relevance
“…We thank Prof. Targer for his interest on our study. 1 We totally agree with him on the concordance between MAFLD (metabolic dysfunction-associated fatty liver disease) and NAFLD (nonalcoholic fatty liver disease), at least among the participants from National Health and Nutrition Examination Surveys (NHANES) 1988-1994 database. 2 We would also like to emphasize that a significant minority of patients with severe liver steatosis go undiagnosed and not captured by the recently proposed MAFLD criteria.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…We thank Prof. Targer for his interest on our study. 1 We totally agree with him on the concordance between MAFLD (metabolic dysfunction-associated fatty liver disease) and NAFLD (nonalcoholic fatty liver disease), at least among the participants from National Health and Nutrition Examination Surveys (NHANES) 1988-1994 database. 2 We would also like to emphasize that a significant minority of patients with severe liver steatosis go undiagnosed and not captured by the recently proposed MAFLD criteria.…”
mentioning
confidence: 69%
“…This research is supported by Chinese National 13th Five-Year Plan's Science and Technology Projects (2017ZX10202201), Fujian Province Health Youth Research Project (2019-1-37). Jiaofeng Huang 1,2…”
Section: Co N Fli C T O F I Nte R E S Tmentioning
confidence: 99%
“…For example, a recent real-world study found that around 15% of patients with NAFLD who failed to meet MAFLD diagnostic criteria exhibited significantly lower non-invasive fibrosis scores than patients with MAFLD. 13,47 Moreover, details of the inclusion or exclusion criteria can be flexibly modified according to the study goal. For example, in observational studies it is feasible to recruit patients with comorbidities of MAFLD and other liver diseases to explore the interaction between these diseases; whereas in clinical trials for new drugs it is also feasible to recruit a subgroup of patients with MAFLD with common metabolic characteristics according to the pharmacological mechanism for enhanced sampling homogeneity.…”
Section: Researchers: Redirecting the Focus On Etiological Heterogementioning
confidence: 99%
“…1 Recently the term metabolic dysfunctionassociated fatty liver disease (MAFLD) has been proposed to better describe liver disease associated with metabolic dysfunction, 2 leading to discussions within the scientific community regarding potential consequent changes in diagnosis, clinical management and drug development. [3][4][5] Until now, NAFLD has been diagnosed by the presence of hepatic steatosis on radiological imaging or biopsy, after ruling out all other reasonable causes (e.g. alcohol consumption).…”
Section: Introductionmentioning
confidence: 99%